Clinicolaboratory profile of children with celiac disease in North India - Singh, Princy; Mittal, Hema Gupta; Dewan, Vivek; Yadav, Tribhuvan Pal (Indian Journal of Child Health, 2022)
Background: Prevalence of celiac disease (CD) has increased worldwide, but there are only few studies reporting clinicolaboratory profile of children with CD. Aim: To study the current clinicolaboratory profile of celiac disease in North Indian children. Methods: This retrospective study was done in pediatric gastroenterology clinic of a tertiary care center of North India. The primary objective was to study clinical and laboratory profile in children with CD. Secondary objective was to find correlation between duodenal biopsy Marsh stage and IgA tissue with tissue transglutaminase antibody (tTG) titers and also with serum hemoglobin, serum iron levels, and severity of anemia. A total of the 54 children fulfilling the diagnostic criteria of CD were included, and details were reviewed and analyzed. Results: Average age of onset of symptoms was 4.7±2.5 years, 80% had onset of symptoms after 2 years of age. Chronic diarrhea (70.3%), pain abdomen (62.9%), and abdomen distention (53.7%) were the most common manifestations. Wasting (38.4% - <5 years, 41.4% in >5 years), stunting (46.3%), rickets (22%), and anemia (90.7%) were common. Serum hemoglobin levels and serum iron levels were inversely correlated to the serum tTG levels and Marsh biopsy staging; though, not significant. Correlation of hemoglobin levels between Marsh stage 3A and 3C was statistically significant (p=0.036). There was no correlation between serum tTG levels and Marsh biopsy staging with anemia and its severity. Conclusion: Gastrointestinal symptoms still remain the most common presentation in children with celiac disease. Malnourishment, anemia, and rickets require special attention in these children.